2010
DOI: 10.33584/jnzg.2010.72.2816
|View full text |Cite
|
Sign up to set email alerts
|

N-leaching in hill country; farmer led research

Abstract: There is scant information on nitrate-N leaching in East Coast hill country. Castlepoint Station, a focus farm in the Wise Use of fertiliser Nitrogen (N) project and in the face of potential restrictions on fertiliser N use, ran a 3 year trial focused on the impacts of N fertiliser on pasture and animal production as well as nitrate leaching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Rainfall falls mainly over the late autumn and winter, with occasional summer rain events. Very regular and high wind run occurs during spring and early summer that constrains pasture growth (Crofoot et al 2010). A 16.6 ha steep north facing paddock (CPS-H) with a resident pasture of crested dogstail (Cynosurus cristatus), rat's tail (Sporobolus africanus) and danthonia (Danthonia sp.)…”
Section: Methodsmentioning
confidence: 99%
“…Rainfall falls mainly over the late autumn and winter, with occasional summer rain events. Very regular and high wind run occurs during spring and early summer that constrains pasture growth (Crofoot et al 2010). A 16.6 ha steep north facing paddock (CPS-H) with a resident pasture of crested dogstail (Cynosurus cristatus), rat's tail (Sporobolus africanus) and danthonia (Danthonia sp.)…”
Section: Methodsmentioning
confidence: 99%
“…Nitrate leaching from applied N fertilisers in pastoral hill country depends on several factors, including fertiliser application rate, timing, weather, slope and soil properties. However, linear increases in N leaching with increased N fertiliser application rates have been reported across NZ hill country farms (Crofoot et al, 2010; Hoogendoorn et al, 2017; Morton & Stevens, 2023). Hoogendoorn et al (2017) estimated an increase of 11%–29% in nitrate leaching at a fertiliser application rate of 20–50 kg N ha −1 , which are rates commonly applied across NZ hill country farms.…”
Section: Effects Of Landscape Features and Land Management Practices ...mentioning
confidence: 99%
“…The accumulation of nutrients, runoff and seepage water on flat (low) slopes makes them CSAs with greater potential for nitrate leaching, due to their accumulation and rapid transport processes. For instance, Crofoot et al (2010) found higher nitrate‐N leaching at low (0–12°) and medium (13–25°) slopes compared with high (>25°) slope in a hill country farm in the Wairarapa region of NZ. Similarly, consistent with the higher soil nitrification potential observed at low slopes (Devantier et al, 2012; Letica et al, 2006), Hoogendoorn et al (2016) reported greater nitrate‐N leaching on low (68 kg ha −1 ) versus medium (5 kg ha −1 ) slopes at Ballantrae Research Farm in NZ.…”
Section: Effects Of Landscape Features and Land Management Practices ...mentioning
confidence: 99%
See 1 more Smart Citation